Outbreak of Pantoea agglomerans Bloodstream Infections at an Oncology Clinic—Illinois, 2012-2013. (6th December 2016) - Yablon, Brian R.; Dantes, Raymund; Tsai, Victoria; Lim, Rachel; Moulton-Meissner, Heather; Arduino, Matthew; Jensen, Bette; Patel, Megan Toth; Vernon, Michael O.; Grant-Greene, Yoran; Christiansen, Demian; Conover, Craig; et al.
Abstract : OBJECTIVE: To determine the source of a healthcare-associated outbreak of Pantoea agglomerans bloodstream infections. DESIGN: Epidemiologic investigation of the outbreak. SETTING: Oncology clinic (clinic A). METHODS: Cases were defined as Pantoea isolation from blood or catheter tip cultures of clinic A patients during July 2012–May 2013. Clinic A medical charts and laboratory records were reviewed; infection prevention practices and the facility's water system were evaluated. Environmental samples were collected for culture. Clinical and environmental P. agglomerans isolates were compared using pulsed-field gel electrophoresis. RESULTS: Twelve cases were identified; median (range) age was 65 (41–78) years. All patients had malignant tumors and had received infusions at clinic A. Deficiencies in parenteral medication preparation and handling were identified (eg, placing infusates near sinks with potential for splash-back contamination). Facility inspection revealed substantial dead-end water piping and inadequate chlorine residual in tap water from multiple sinks, including the pharmacy clean room sink. P. agglomerans was isolated from composite surface swabs of 7 sinks and an ice machine; the pharmacy clean room sink isolate was indistinguishable by pulsed-field gel electrophoresis from 7 of 9 available patient isolates. CONCLUSIONS: Exposure of locally prepared infusates to a contaminated pharmacy sink caused the outbreak. Improvements in parenteral medication preparation, including moving chemotherapy preparation offsite, along with terminal sink cleaning and water system remediation ended the outbreak. Greater awareness of recommended medication preparation and handling practices as well as further efforts to better define the contribution of contaminated sinks and plumbing deficiencies to healthcare-associated infections are needed. Infect Control Hosp Epidemiol 2017;38:314–319